Effect of the addition and processing of glass polishing waste on the durability of geopolymeric mortars - de Azevedo, A.R.G. (Elsevier Ltd, 2021)
The waste from the flat glass polishing process for civil construction is generally discarded in landfills. Despite some researchers evaluating its application in the development of alternative building materials, its added value is still a barrier. The objective of this research is to evaluate the physical-mechanical behavior of the addition of glass polishing waste on the durability of geopolymeric mortars to be used for small external structural repairs and their processing methods. Cylindrical specimens (50 Ã 100 mm) were made with metakaolin (MK) and natural sand as precursors, whereas a mixture of NaOH in pearls + glass polishing waste, dissolved in water in two different orders (A: dry mixing of both activators and B: NaOH was dissolved in water and then the glass waste was added) was used as an alkaline solution, in addition to a reference mixture (without waste). The dosage used a SiO2/Al2O3 ratio = 2.5 and 3.0. The specimens were subjected to ambient and thermal curing (60 Â°C) for 7 days and then submitted to laboratory for measuring the durability of wetting and drying cycles, saline environment and thermal shock. It can be observed that in the evaluation of wetting and drying cycles, the type A mixture with a molar ratio of 3.0 in ambient cure obtained a weight loss of 10 , while in mechanical strength with a molar ratio of 2.5 and thermal cure the reduction was 27.34 . Meanwhile, in the durability to salt exposure, both processing conditions were satisfactory, with a molar ratio of 3.0, with type A and thermal cure with a loss of mass of 11.25 . In the evaluation of thermal shock, the mixture with the smallest loss of mechanical strength was the molar ratio of 2.5, type A with ambient cure. It can be concluded that forthe conditions evaluated, the mixture with a molar ratio of SiO2/Al2O3 = 2.5, using type A processing in the ambient cure, presented the smallest losses in mass and mechanical strength in comparative terms, adapting to the values of literature for mortars. Â© 2021 The Author(s)